The Comparison of Assessment Scores Between Modules Taught Face to Face and Online in Undergraduate Medical Students During COVID-19 Pandemic (Medical Forum Monthly, 2021)
Objective: To study the comparison of the Physiology test score and overall test scores between modules taught face to face and online.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Jinnah Medical and Dental College, Karachi from Jan 2021 to March 2021.Materials and Methods: The study participants included 2nd year medical students. There were total 96 MBBS students. Out of 96, 90 students attempted the Neuroscience module test and 88 attempted the Endocrine module test. The Neuroscience module was taught face to face on campus before the lockdown for COVID 19 pandemic was implemented. For the endocrine module, online recorded lectures were sent to students. In both the modules, test was conducted online. The Physiology test scores as well as the overall test scores were compared.Results: The Physiology test score was higher (54.64±20.12) in Neuroscience module that was taught face to face as compared to (31.42±26.00) in Endocrine module that was taught online. Regarding the overall module test score, Neuroscience has a higher score (62.12±13.45) as compared to Endocrine (52.06±16.81). The overall passing percentage was (74%) in Neuroscience module and (48%) in Endocrine module.Conclusion: The medical students had a higher test score in module taught by face to face teaching method as compared to the module taught online.